Transport of Ligand Coordinated Iron and Chromium through Cation-Exchange Membranes. Issue 6 (1st June 2022) - Saraidaridis, James D.; Darling, Robert M.; Yang, Zhiwei; Shovlin, Christopher; Fortin, Michael; Robb, Brian H.; Waters, Scott E.; Marshak, Michael P.
Abstract : Fluxes of negatively charged ligand-coordinated iron, Fe(CN)6 3/4-, and chromium, CrPDTA 1/2−, through two promising commercial cation-exchange membranes, Aquivion E87–05S and Fumasep E-620(K), were measured as functions of current density. The magnitude of the partial current density reached a maximum of − 43 μ A cm −2 at the maximum applied current density magnitude of − 43 mA cm −2 for Fe(CN)6 3/4− transport through Aquivion, or 0.1% of the total current density. Fumasep E-620(K) blocks practically all crossover of both compounds. Both membranes sorb more Fe(CN)6 3/4− and CrPDTA 1/2− than predicted by Donnan equilibrium, and low crossover rates can be attributed mainly to slow diffusion, not charge-based rejection of co-ions. The magnitude of the diffusion coefficient appears to correlate with hydraulic permeability. Although Aquivion E87–05S and Fumasep E-620(K) have significant and observable differences in membrane crossover rates, cells built with the DI-soaked membranes offer similarly high coulombic efficiency, indicating the relatively small contribution that crossover makes to inefficiency over a single cycle.